Factors Associated with Treatment Defaulter Among Tuberculosis Patients Registered Under RNTCP In Surat City, Gujarat - Khushbu Patel; Kinjal Patel; Dhwani Patel; Prakash Patel; Swati Patel; RK Bansal (Medsci Publications, 2016)
Introduction: Defaulting from treatment has been one of the major drawbacks to treatment management and represents an important challenge for TB control program. This study was conducted to assess factors associated with treatment defaulter among TB patients in Surat city. Method: All TB patients registered RNTCP in Surat city from July to August 2016 were include in study. This study was comparing previously treatment defaulter and newly diagnosed TB patients. Result:  In this study observed that male gender, age more than 30 years, migrant status, illiteracy unskilled labour word, lower socio-economic class, tobacco consumption, alcohol habite were significantly associated (P<0.05) with previous treatment defaulter compare to newly diagnosed cases associated factors with defaulter in Surat city. Conclusion: We conclude that previous treatment defaults are more in cases with more than 30 years, male, migrant, from low socioeconomic strata, illiterate, engaged in daily unskilled labour work, having habit of tobacco & alcohol, and exposed to passive smoking.